2022
DOI: 10.1002/adom.202102616
|View full text |Cite
|
Sign up to set email alerts
|

Homeotropic Concentric Helix Orientations in Chiral Nematic Cellulose Nanocrystal Films by Local Magnetic Fields

Abstract: Many fascinating device applications of chiral nematic materials are determined by their helical axis orientations. Cellulose nanocrystals (CNCs) self‐assemble producing left‐handed chiral nematic films with predominant planar textures. While varied techniques have been exploited to tune the helical axis orientations, it remains challenging to produce concentrically aligned chiral nematic state. Herein, the authors report novel findings that left‐handed chiral nematic CNC films formed with homeotropic concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 60 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Cellulose nanocrystals (CNCs), due to their intriguing hierarchical chirality, especially that derived from self-assembled cholesteric structures, are considered as powerful chiral nanomaterials to manufacture CPL-active platform. [43,[147][148][149][150][151][152][153] The hydroxyl and charged groups on the CNCs surface can form non-covalent bonds with achiral luminophores, such as organic luminophores, [16,149,[154][155][156][157] quantum dots, [158][159][160] carbon dots (CDs), [161][162][163][164][165] upconverting nanoparticles, [166] and so on. [167,168] The CPL performance of CNCs-based materials is summarized in Table 3.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cellulose nanocrystals (CNCs), due to their intriguing hierarchical chirality, especially that derived from self-assembled cholesteric structures, are considered as powerful chiral nanomaterials to manufacture CPL-active platform. [43,[147][148][149][150][151][152][153] The hydroxyl and charged groups on the CNCs surface can form non-covalent bonds with achiral luminophores, such as organic luminophores, [16,149,[154][155][156][157] quantum dots, [158][159][160] carbon dots (CDs), [161][162][163][164][165] upconverting nanoparticles, [166] and so on. [167,168] The CPL performance of CNCs-based materials is summarized in Table 3.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%
“…[176] This strategy could achieve the generation of CPLactive polyfluorene aggregate by completely removing dialkylpolysilane. The authors found that the resulting heteroaggregates might be composed of one polyfluorene chain and two Fluorescent organic dyes Solid film -0.68 [16] Fluorescent organic dyes Solid film -0.28 [157] Polyacetylene Solid film -0.65 [155] Quinine sulfate Solid film 38% 0.58 [149] Quinine sulfate dihydrate Solid film -0.51 [154] PEI Solid film -0.025 [156] CdSe/CdS quantum rods Solid film -0.45 [148] ZnS/CdSe quantum dots Solid film -0.48 [158] ZnS/CdSe quantum dots Solid film -0.84 [159] Silicon quantum dots Solid film -0.25 [160] Carbon dots Solid film 30.22% 0.74 [161] Carbon dots Aqueous dispersions -0.2 [162] Carbon dots Solid film 5.2% 0.27 [163] Carbon dots Solid film 2.8% 0.66 [164] Carbon dots Solid film -1.47 [165] Upconverting nanoparticles Solid film -0.156 [166] Lanthanide complexes Solid film 66.7% 0.36 [167] Perovskite nanocrystals Solid film 43.1% 0.057 [168] Gold nanoclusters Solid film -0.287 [172] Silver nanoclusters Solid film 15.96% 0.12 [173] NaGdF4Yb 3+ , Er 3+ @ Carbon dots Solid film -0.84 [152] polysilanes chains. Wei et al described the preparation of polyether-based cholesteric liquid crystalline copolymers containing chiral cholesteryl, cross-linkable allyl, as well as, cyano-biphenyl mesogenic groups moieties by anionic ring-opening polymerization.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%
“…Cellulose nanocrystals (CNCs) isolated from the natural cellulose of wood and nonwood origin by sulfuric acid hydrolysis or 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-mediated oxidation show a set of fascinating properties including hierarchical chirality and complex superstructures. The most outstanding feature of sulfuric acid hydrolyzed CNCs is the ability to self-assemble into a left-handed chiral nematic organization that displays circular shape birefringence. , This leads to a remarkable range of advanced materials including one-dimensional photonic band gap materials, responsive structure-color materials, , light management materials, and bioinspired structural materials. , On the other hand, the self-assembly of sulfuric acid hydrolyzed CNCs forms a transient nematic-like mesostructure that can be arrested kinetically. , MacLachlan and co-workers reported that a quasi-nematic structure of sulfuric acid hydrolyzed CNCs and the silica imprint function as depolarizing filters for CPL and can be used to pattern chiral photonic CNC films; however, the depolarization mechanism was not provided . Mendoza-Galván and co-workers described the depolarizing effects of chiral nematic structures in CNC films, which also gave a referable analysis. In contrast to the sulfuric acid hydrolysis method, CNCs obtained by hydrochloride acid hydrolysis have similar particle sizes and shapes but no other external group influence.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral photonic CNC films have the intrinsic ability to divide incident light into photonic-bandgap-based left-handed circularly polarized reflected light and right-handed circularly polarized transmitted light, and to transform spontaneous luminescence to circularly polarized luminescence. Some interesting CNC-based circularly polarized light materials have been developed as well as more examples including optically ambidextrous reflection and luminescence materials, , handedness tunable circularly polarized light materials, , plane-lateral circularly polarized light materials, and room-temperature circularly polarized phosphorescent materials. , The highest reported | g lum | value of right-handed circularly polarized luminescence inside the bandgap is ca. 0.8, which is below 2, and left-handed circularly polarized luminescence fails to occur at the band edge.…”
Section: Introductionmentioning
confidence: 99%